-8v+6(v-5)=-28

Simple and best practice solution for -8v+6(v-5)=-28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8v+6(v-5)=-28 equation:


Simplifying
-8v + 6(v + -5) = -28

Reorder the terms:
-8v + 6(-5 + v) = -28
-8v + (-5 * 6 + v * 6) = -28
-8v + (-30 + 6v) = -28

Reorder the terms:
-30 + -8v + 6v = -28

Combine like terms: -8v + 6v = -2v
-30 + -2v = -28

Solving
-30 + -2v = -28

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + -2v = -28 + 30

Combine like terms: -30 + 30 = 0
0 + -2v = -28 + 30
-2v = -28 + 30

Combine like terms: -28 + 30 = 2
-2v = 2

Divide each side by '-2'.
v = -1

Simplifying
v = -1

See similar equations:

| 5ln(3x)+6=31 | | (3x+1)(4x+1)(6x+1)(12x+1)=2 | | -9.5x+39.9=7.5 | | 10-6y+4y=9 | | -0.9+3.6x=0.18 | | 7x+2x+36=180 | | 90=8f | | 4tan(t)+9=8 | | -11m=77 | | 4x-600=600 | | 5x*3+5=10 | | 0.04(150+0.25y)-0.08y=-36 | | 6(a+7)=7(a+9) | | 9x-21+9=2(50-x) | | y=-3*-3+3 | | -29=7q+27 | | 5(x+4)-2=33 | | -29= | | y=-3*-6+3 | | 12a=49 | | 5q-17=43 | | H=6+75t-16t^2 | | 6w^2+10w^2=c^2 | | (4x+4)= | | y^2-4x^2+8y=0 | | 4m-16=-32 | | 4(14x)=7x+40 | | -11c+10=45 | | 6sin(4x)=5 | | 1.5*sin(93.3-x)=2.7*sin(x) | | (-5a-7b)-(-7a-9b)= | | 9a-7a= |

Equations solver categories